Anhydrous microwave synthesis as efficient method for obtaining model advanced glycation end-products - Bronowicka-Szydełko, Agnieszka; Madziarska, Katarzyna; Kuzan, Aleksandra; Lewandowski, Łukasz; Adamiec-Mroczek, Joanna; Pietkiewicz, Jadwiga; Tota, Maciej; Ziomek, Maciej; Stach, Wojciech; Trocha, Tymoteusz; Piersiak, Marcin; Pachana, Maciej; et al. (Frontiers in Molecular Biosciences, 2024)
IntroductionAdvanced glycation end-products (AGEs) are capable of stimulating oxidative stress and inflammation. This study investigates the synthesis of medium crosslinked AGEs (the most optimal form of AGEs because of soluble in water, used in many assays as markers) and their biochemical properties.MethodsOne of model protein–myoglobin from horse heart muscle (MB) and a chosen respective glycation factor – D-melibiose (mel), acrolein (ACR), D-glucose (glc), 4-hydroksynonenal (4HNE), trans-2-nonenal (T2N), methylglyoxal (MGO) – were subjected to high temperature water synthesis (HTWS) and high temperature microwave synthesis in anhydrous conditions (HTMS). The syntheses were deliberately carried out in two different conditions to check whether adding an additional energy source (microwaves) while lowering the temperature and shortening the reaction time would allow for more effective obtaining of medium-cross-linked AGEs, monitored with SDS-PAGE. Products were analyzed using fluorescence measurements, Enzyme-Linked Immunosorbent Assay (ELISA) and immunoblotting tests and electrophoretic mobility shift assay to evaluate their ability to activate nuclear factor kappa-light-chain-enhancer (NF-κB).ResultsMedium cross-linked AGEs were more efficiently obtained in HTMS. Fluorescence was high for MB-ACR, MB-T2N and MB-glc products. Anti-MAGE antibodies showed reactivity towards MB-mels of HTMS and HTWS, and the MB-4HNEs from HTMS. HTWS products, apart from MB-ACR, did not activate NF-κB, whereas MB-ACR, MB-4HNE, MB-mel, and MB-T2N products of HTMS strongly activated this factor that indicates their strong pro-inflammatory properties.ConclusionHTMS is a fast and efficient method of synthesizing medium cross-linked AGEs.